IMPLEMENTASI PERATURAN BUPATI NOMOR 38 TAHUN 2012 TENTANG IZIN USAHA PASAR MODERN DAN PASAR TRADISIONAL DI KABUPATEN SIDOARJO - Jannah, Siti Nur (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2014)
This research explores the role of Sidoarjo government in regulating the guidance and supervision of the management of traditional and modern markets. The reaserach uses descriptive-qualitative approach and attempts to answer two main questions, are:first, how is the implementation of the decree number 38 year 2012, concerning the business license of traditional and modern markets? Second, are there any infringements of the license committed by modern markets’ owners? The study has indicated that, in the implementation of local government’s regulations, there has been always a strong influence of the modern market. approval of the location permit has been always colored by gratification. Second, there are infringements of the decree committed by the owner of the modern markets with the absence of information dissemination to the small stallsas well as money politics shared to the citizens as their compensation.